Urinary bladder paraganglioma: a clinical dilemma in diagnosis and management: our experience at a tertiary care center - Kriplani, Akshay; Jain, Deep; Kulshreshtha, Mayank; Jayadeva Reddy, Suraj; Pandit, Shruti; Reddy, Bathi Sourabh; Sachdev, Gurvansh Singh; Hiremath, Vivekanand Kedarlingayya; Chawla, Arun (International Journal of Research in Medical Sciences, 2022)
Urinary bladder paraganglioma (UBP) are rare neuroendocrine tumors with variable biological behavior. High index of suspicion in the preoperative evaluation would enable the clinician to formulate appropriate management of the rare tumors. Clinical and pathological data of seven cases evaluated and treated as per a devised protocol for suspected bladder paraganglioma from 2008 to 2019 was retrospectively reviewed. Among the seven cases, UBP’s were predominantly seen in middle aged men. Most of these presented with storage symptoms (85.71%; n=7) and gross painless hematuria (42.85%; n=3). Three patients were hypertensives and post-micturition syncope was seen in two patients. Among the seven patients two patients had functionally active tumors confirmed by elevated urinary and serum markers for catecholamine excess. Functional tumors, nonfunctional tumors involving uretero-vesical junction or broad based polypoidal tumor were considered for partial cystectomy. Other small nonfunctional tumors underwent trans-urethral resection of bladder tumour (TURBT). Follow up protocol included repeat ultrasound, check cystoscopy and completion TURBT at one month and annually thereafter. Repeat urinary catecholamines at 1 month was done in functional UBP. Cystoscopic examination of a bladder lesion which are solid, sessile and predominantly intramural, a prior to a definitive planned surgery may differentiate UBP from urothelial cancer. Most of the non-functional UPB are diagnosed by histopathological examination. In symptomatic cases, functional evaluation with biochemical estimation of catecholamine excess allow better treatment planning and avoiding intraoperative hemodynamic instability. Due to high recurrence rate life-long follow-up despite complete excision is strongly recommended.